Insight into the Relationship between the Causes of Off-Odour and Microorganism Communities in Xuanwei Ham - Haoyi Wang; Xiaoyu Yin; Lu Zhang; Xuejiao Wang; Jiliang Zhang; Rongxin Wen; Jianxin Cao (Foods, 2024)
To expound on the correlation between the microorganism communities and the formation of off-odour in Xuanwei ham, the microorganism communities and volatile compounds were investigated in the biceps femoris (BF) and semimembranosus (SM) of Xuanwei ham with different quality grades (normal ham and spoiled ham). The single molecule real-time sequencing showed that differential bacteria and fungi were more varied in normal hams than in spoiled hams. Headspace solid-phase microextraction–gas chromatography (HS-SPME-GC-MS) results indicated that aldehydes and alcohols were significantly higher in spoiled hams than those in normal hams (p < 0.05). The off-odour of spoiled hams was dominated by ichthyic, malodourous, sweaty, putrid, sour, and unpleasant odours produced by compounds such as trimethylamine (SM: 13.05 μg/kg), hexanal (BF: 206.46 μg/kg), octanal (BF: 59.52 μg/kg), methanethiol (SM: 12.85 μg/kg), and valeric acid (BF: 15.08 μg/kg), which are positively correlated with Bacillus cereus, Bacillus subtilis, Bacillus licheniformis, Pseudomonas sp., Aspergillus ruber, and Moraxella osloensis. Furthermore, the physicochemical property and quality characteristics results showed that high moisture (BF: 56.32 g/100 g), pH (BF: 6.63), thiobarbituric acid reactive substances (TBARS) (SM: 1.98 MDA/kg), and low NaCl content (SM: 6.31%) were also responsible for the spoilage of hams with off-odour. This study provided a deep insight into the off-odour of Xuanwei ham from the perspective of microorganism communities and a theoretical basis for improving the flavour and overall quality of Xuanwei hams.